Formation of Sn‐Induced Nanowires on Si(557) (Phys. Status Solidi B 10/2019). Issue 10 (23rd October 2019) - Jäger, Monika; Pfnür, Herbert; Fanciulli, Mauro; Weber, Andrew P.; Dil, Jan Hugo; Tegenkamp, Christoph
Abstract : The growth of Sn on Si(557) has been studied by M. Jäger et al. (article no.1900152 ) in order to elucidate the possibility to form defined nanowires. For low Sn‐coverage, the surface structure consists of ca. 3 nm wide (111) terraces covered with the Sn structure separated by triple steps, similar to Ag/Si(557). The cover image shows a 3D rendered scanning tunneling microscope image of such Sn‐nanowires grown on vicinal Si(111). The confinement quenches the insulating Mottstate, as revealed by angle‐ and spin‐resolved photoemission experiments, yielding metallic surface states at 40 K.